Effect of Trade Diversification on Economic Growth of ECOWAS Countries - Kayode, Ogunyemi Joseph; David, Dare Funso; Adeyinka, Adewole Joseph (American Economic & Social Review, 2019)
This study investigated the effect of trade diversification on economic growth of ECOWAS countries. The study has looked at the determinants of exports and imports in some selected ECOWAS countries. The selected ECOWAS countries are Benin, Ghana, and Nigeria. The employed a model form of the GMM estimator was adopted but the empirical validation shall be based on ordinary panel regression. The study revealed that the activities of the main sector when rated as a percentage of the gross domestic product is a significant factor that influences the exports and imports in these selected countries. This means that the activities done in the main sector of these economies have significant effect on the value of exports and imports. The activity of the main sector is huge and voluminous enough to accommodate some level of significant imports in order to assist production which will also be exported. The study has also revealed that the service sector is also a significant factor that influences the exports and imports of these selected ECOWAS countries. Many experts are imported into the service sector of these countries and thus these served as a significant factor that possess influence on the performance of exports and imports in the countries. There is a negative and weak correlation between primary exports and service as a percentage of GDP. Invariably, it can be said that the level of primary exports may not be related with the service sector, thus, the association is expected. The main sector performance is found to be positively correlated with the primary exports in the selected ECOWAS countries. The author then suggested that there is urgent need for ECOWAS states to place more emphasis on the exports of manufacturers’ products and make efforts to reduce concentration on exports of primary (agriculture and fuel) products. This will help improve their international trade performance especially with respect to reducing term of trade losses and unfavorable shocks in foreign earnings. Also, the region should focus on production of products for domestic need; in doing this, the ECOWAS states will escape the trap of homogenous export and foster more intra-trade links. The region should see production as major objective rather than exports; this enhances industrial activities and innovations in the region. This attempt retains economic gains of resource within the region and foster economic well-being, the critical mass of ECOWAS challenge is weak productive capacity, this has accentuated the progress of the member states and the sole cause of social and economic evils within the region. ECOWAS should see exports as originating from domestic sufficiency.